INTELIGENCIA EMOCIONAL Y FORMACIÓN PROFESIONAL DE LOS ESTUDIANTES DE LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN, HUMANAS Y TECNOLOGÍAS DE LA UNIVERSIDAD NACIONAL DE CHIMBORAZO, RIOBAMBA. PERÍODO ACADÉMICO OCTUBRE 2018 - MARZO 2019. - Buenaño Ocaña, Carmen Alexandra (2019)
The objective of this research work was to determine the relationship between Emotional Intelligence and Vocational Training of the 39 students, including 10 men and 29 women, of the eighth semester of the Faculty of Education, Humanities and Technologies of the National University of Chimborazo. ; Emotional Intelligence is the ability to identify, understand and manage one's emotions correctly, as well as interpersonal relationships, in addition managing stress or overcoming various obstacles. Vocational Training is the set of learning that people receive in order to enter the working world. The methodology used was of non-experimental design, since the variables were not manipulated. The type of research is descriptive and correlational. For the objectives it is basic; for the place of field and bibliographic; the type of study is transversal. The sample was intentional non-probabilistic. The technique for data collection was the survey, and the instrument was the Ad hoc questionnaire. It was determined that there is a correlation between Emotional Intelligence and Vocational Training, therefore having a high level of Emotional Intelligence is important to maintain adequate interpersonal relationships, and for the workplace, since nowadays not only qualified personnel is required to hold positions but also to face problems in an assertive manner, that is; that they know how to control their emotions, that they possess the ability to soften expressions of anger, fury or irritability, taking into account that this is essential in the teaching task.